Credit and Financial Revenue Award: A Tool for Economic and Management Analysis - de Amorim, Gabriel (REGEPE Entrepreneurship and Small Business Journal, 2019)
Objective: The objective is to propose a model analyzes several variables considered pertinent to the decision, such as time of receipt, delinquency rate over term sales, inflation and/or total cost of capital of the company. Context / Reality Investigated: Small companies are usually created by the need of their entrepreneurs, who dedicate themselves to its management often without the project adapted to the reality of the market in which it is inserted. Commonly, to increase sales volume, these companies adopt credit sales without the use of an intermediary. Diagnosis / Situation-problem / Opportunity: The immersion in this scenario made it necessary to use a tool to mark the decision whether or not to grant the loan portfolio to specialized management companies, whose expertise allowed them to assume the management of clients, concentrating small businesses to develop in their core business, without having to dedicate themselves to also analyzing their credit management policy. The proposed model analyzes several variables considered pertinent to the decision, such as time of receipt, default rate on term sales, inflation and / or total capital cost of the company. Results: The result of that is the default and difficulty in honoring commitments assumed whose value has the result that values below 1, calculated, indicate better net (financial) results with the maintenance of the own management. Already values above 1 indicate the best economic-financial performance of the business with the granting of capital management to specialized companies. The model was tested in cash flow simulations and showed consistency in all of them. In addition, it also applies to any business.